Heart and lungs protection technique for cardiac surgery with cardiopulmonary bypass - Pichugin, Vladimir; Melnikov, Nikolay; Olzhayev, F.; Medvedev, Alexander; Jourko, Sergey; Gamzaev, Alishir; Chiginev, Vladimir (Central Asian Journal of Global Health, 2014)
Cardioplegic cardiac arrest with subsequent ischemic-reperfusion injuries can lead to the development of inflammation of the myocardium, leucocyte activation, and release of cardiac enzymes. Flow reduction to the bronchial arteries, causing low-flow lung ischemia, leads to the development of a pulmonary regional inflammatory response...
Keywords: constant coronary perfusion; pulmonary artery perfusion; cardiopulmonary bypass; Research Subject Categories::MEDICINE